Sugar in the British Atlantic World 1650-1720 - Goodall, M (2022)
This DPhil thesis, Sugar in the British Atlantic World 1650-1720, seeks to analyse the effect and extent of the sugar trade in the seventeenth century. By 1700, sugar was one of the most important commodities in Europe. It was the driving force behind the trafficking of hundreds of thousands of people, huge accumulation of capital, the growth of international trade, and a number of important subsidiary industries. The development of the institution of chattel slavery and its influence on the history of capitalism has been the subject of many scholarly investigations, however there has been comparatively little work done on the consumption on sugar itself. The thesis, therefore, examines trade in sugar across the Atlantic Ocean and tracks the ways in which the good was consumed.